(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article provides a detailed overview of the legal status, rights, and obligations of liability-limited organizations and additional liability companies, as well as their compliance with legal and regulatory documents, the formation of their charter capital, and the establishment of internal audit services.